Face Recognition Deficits in a Patient With Alzheimer's Disease: Amnesia or Agnosia? The Importance of Electrophysiological Markers for Differential Diagnosis - Mazzi, Chiara; Massironi, Gloria; Sanchez-Lopez, Javier; De Togni, Laura; Savazzi, Silvia (Frontiers in Aging Neuroscience, 2020)
Face recognition deficits are frequently reported in Alzheimer’s disease (AD) and often attributed to memory impairment. However, it has been hypothesized that failure in identifying familiar people could also be due to deficits in higher-level perceptual processes since there is evidence showing a reduced inversion effect for faces but not for cars in AD. To address the involvement of these higher processes, we investigated ERP neural correlates of faces in an AD patient showing a face recognition deficit. Eight healthy participants were tested as a control group. Participants performed different tasks following the stimulus presentation. In experiment 1, they should indicate whether the stimulus was either a face or a house, or a scrambled image. In experiments 2 and 3, they should discriminate between upright and inverted faces (in Experiment 2 stimuli were faces with neutral or fearful expressions, while in Experiment 3 stimuli were famous or unfamiliar faces). Electrophysiological results reveal that the typical face-specific modulation of the N170 component, which is thought to reflect the structural encoding of faces, was not present in MCG, despite being affected by the emotional content of the face implicitly processed by MCG. Conversely, the N400 component, which is thought to reflect the recruitment of the memory trace of the face identity, was found to be modulated implicitly in MCG. These results may identify a possible role for gnosic processes in face recognition deficits in AD and suggest the importance of adopting an integrated approach to the AD diagnosis considering also electrophysiological markers.